2008
DOI: 10.1002/pssb.200844049
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in SiOx films annealed under enhanced hydrostatic pressure

Abstract: The effect of enhanced hydrostatic pressure (HP, (10–12) × 108 Pa) on thermally stimulated phase decomposition of silicon suboxide layers processed at 450–1000 °C was investigated by infrared spectroscopy and photoluminescence measurements. HP stimulates decomposition of non‐stoichiometric SiOx most efficiently at about 450 °C. In spite of enhanced SiOx decomposition, visible photoluminescence appears in HP‐treated samples at higher annealing temperatures in comparison to those annealed under ambient pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Of course that presents only a very rough estimation but shows that only 10–20% of implanted Si atoms become visible as clusters. The rest is still dispersed in the SiO 2 matrix, better said SiO x matrix 21. We may describe this incomplete phase separation by the rate equation: with the stoichiometric factors 0 ≤ x 1 < x 2 ≤ 2 before ( x 1 ) and after ( x 2 ) ongoing phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…Of course that presents only a very rough estimation but shows that only 10–20% of implanted Si atoms become visible as clusters. The rest is still dispersed in the SiO 2 matrix, better said SiO x matrix 21. We may describe this incomplete phase separation by the rate equation: with the stoichiometric factors 0 ≤ x 1 < x 2 ≤ 2 before ( x 1 ) and after ( x 2 ) ongoing phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…The rest is still dispersed in the SiO 2 matrix, better said SiO x matrix. We may describe this incomplete phase separation [16] by the rate equation:…”
Section: Resultsmentioning
confidence: 99%
“…As samples we have used amorphous, thermally grown SiO 2 layers, 500 nm thick, wet oxidized at 1100 °C on Si substrate. The layers are of microelectronic quality and doped by Si + ions with an energy of 150 keV and a dose of 5×10 16 ions/cm 2 leading to an atomic dopant fraction of about 4 at% at a mean depth of about 200 nm, see [3]. Afterwards a post-implantation thermal annealing has been performed at temperatures T a = 700-1300°C for 60 minutes in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] It has been found that the PL intensity can be strongly affected by the high temperature ͑HT͒-high pressure ͑HP͒ treatment of the thermally grown oxygen-deficient as well as of stoichiometric silicon dioxide films. 12,13 Some information on the HT-HP induced effects in SiON can also be found in literature. 14,15 In this work, we report an extended research on the silicon oxynitride films with HT-HP treatment.…”
mentioning
confidence: 99%